Sikap guru Bahasa Melayu terhadap penggunaan teknologi maklumat dan kKomunikasi (ICT) dalam pengajaran di Sekolah-sekolah Rendah di Bintulu, Sarawak - Chung, Hui Ching,Melvina; Jamaludin Badusah, (penerbit ukm, 2010)
This is an exploratory study to identify the attitudes of Malay Language teachers’ who teach in primary school in Bintulu area towards the usage of Information Technology and Communication (ICT) in teaching process. This research also studies the connection between attitude and knowledge and Malay Language teachers’ skill toward the usage of ICT in teaching process. Besides, this research also looks at the attitude towards the use of ICT according to types of school and ICT course that has been attended by the teachers. There are 105 Malay Language teachers who teach at 12 primary schools in Bintulu, 7 are Sekolah Kebangsaan (SK) and 5 are Sekolah Jenis Kebangsaan (SJK) who will be the research sample. This research is conducted by using a set of questionnaire which has been edited by Fairose (2006). The data collected analysed using SPSS programme version 12.0.The result of the research showed that Malay Language teachers’ attitudes towards the usage of ICT in teaching are positive. However, Malay Language teachers’ knowledge and skill are still at average level. This result showed that there are no differences significant of teachers’ attitude towards the use of ICT in teaching process according to types of school. However, there are different significant between teachers’ attitude who have attended ICT course and teachers who never attend ICT course.